ANALISIS KARAKTER RASA INGIN TAHU SISWA PADA TEMA 8 KELAS III SEKOLAH DASAR - Sururin Ayu Wardani; Nugrananda Janattaka (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
Character education is a process of transforming life values to be developed in a person's personality, so that it becomes a habit in that person's life behavior, one of which is the character of curiosity. The results of pre-observations conducted on third grade students at SD Negeri 3 Jabalsari showed low student curiosity with the following indicators: (1) students rarely asked questions, (2) students did not want to find answers, (3) students were not active in discussions. groups, (4) students are less enthusiastic in the learning process, (5) students do assignments as they please. This study aims to describe the results of the analysis of the curiosity character of third grade students at SD Negeri 3 Jabalsari on thematic learning theme 8. This study uses qualitative methods and uses a descriptive qualitative approach. The data collection technique of this research used observation, interviews for teachers and students, and questionnaires for students. The results of this study indicate that the value of the curiosity character of students on theme 8 classically gets a score of 55%, this shows the curiosity of third grade students of SD Negeri 3 Jabalsari is quite good. In this study, the most prominent indicator is the indicator of attention to the object being observed with an average percentage score of 78%, while for indicators that are not prominent in this study are the indicators of asking for each activity step with an average percentage score of 35%.